Studi Penentuan Lokasi Alternatif Tempat Pembuangan Akhir (TPA) Sampah di Kabupaten Cianjur - Tegar Aditama; Hani Burhanudin (Bandung Conference Series: Urban & Regional Planning, 2022)
Abstract. Garbage is a serious problem in Cianjur Regency. The Department of Environment (DLH) of Cianjur Regency itself is considering a new land for the Final Disposal Site (FDS). The Department of Environment (DLH) of Cianjur Regency projects that the land for the new TPA will be around 25 hectares. The Cianjur Regency Government plans 2 new TPA locations in Cikadu Subdistrict and Cikalong Kulon Subdistrict. The condition of the Pasir Sembung Final Disposal Site (FDS) is already mounting and efforts are being made to reduce the volume of waste by dredging the waste and turning the waste into a pedestal or road. Cianjur Regency only has one final disposal site for waste, namely the Pasir Sembung Final Disposal Site (FDS). This TPA has been operating since 1975. The purpose of this research is to find a new FDS location in Cianjur Regency. The method used in this research is descriptive quantitative method. Data collection techniques through observation and questionnaires. The analytical method in this study uses the overlay analysis method and the hierarchy process analysis (AHP) and uses (SNI) No.19-3241-1994 as a research reference. The results of this study are the chosen location of the TPA Garbage in Cikadu District, which is in Cikadu Village, Mekarjaya Street with an area of ​​240 Ha and Cikalong Kulon District, which is in Padajaya Village, Mariwati Street with an area of ​​4.78 Ha. Abstrak. Sampah menjadi masalah yang serius di Kabupaten Cianjur. Dinas Lingkungan Hidup (DLH) Kabupaten Cianjur sendiri tengah mempertimbangkan lahan baru untuk Tempat Pembuangan Akhir (TPA). Pihak Dinas Lingkungan Hidup (DLH) Kabupaten Cianjur memproyeksikan lahan untuk TPA baru sekitar 25 Ha. Pemerintah Kabupaten Cianjur merencanakan 2 calon lokasi TPA yang baru di Kecamatan Cikadu dan Kecamatan Cikalong Kulon. Kondisi Tempat Pembuangan Akhir (TPA) Pasir Sembung sudah menggunung dan dilakukan upaya untuk mengurangi volume sampah dengan pengerukan sampah dan sampah tersebut menjadi alas atau jalan. Kabupaten Cianjur hanya memiliki satu tempat pembuangan akhir untuk sampah yaitu di TPA Pasir Sembung. TPA ini beroperasi sejak tahun 1975. Tujuan dari penelitian ini yaitu untuk mencari lokasi TPA yang baru di Kabupaten Cianjur. Adapun metode yang digunakan dalam peneliltian ini adalah metode kuantitatif deskriptif. Teknik pengumpulan data melalui observasi dan kuesioner. Metode analisis dalam penelitian ini menggunakan metode analisis overlay dan analisis hierarcy process (AHP) serta menggunakan (SNI) No.19-3241-1994 sebagai acuan penelitian. Hasil dari penelitian ini adalah terpilihnya lokasi TPA Sampah di Kecamatan Cikadu, yang berada di Desa Cikadu, Jalan Mekarjaya dengan luasan 240 Ha dan Kecamatan Cikalong Kulon, yang berada di Desa Padajaya, Jalan Mariwati dengan luasan 4,78 Ha.